Improved Renal Allograft Survival for Pre-Emptive Paediatric Renal Transplant Recipients in the United Kingdom. (July 2018) - Marlais, Matko; Martin, Kate; Marks, Stephen D
Abstract : Objectives: The aim of this study was to investigate whether being on dialysis at the time of renal transplantation affected renal allograft survival in paediatric renal transplant recipients (pRTR). Methods: Data were obtained from the UK Transplant Registry (NHS Blood and Transplant) on all children (aged <18 years) who received a kidney only transplant between 1 January 2000 and 31 December 2015. Baseline demographic data were collected, including dialysis modality at the time of renal transplantation (none vs peritoneal dialysis vs haemodialysis). Kaplan-Meier estimates of 5-year renal allograft survival were calculated, as well as Cox regression modelling accounting for donor type. The relationship between time on dialysis and renal allograft survival was also examined. Results: 2, 038 pRTR were analysed: 607 (30%) were pre-emptively transplanted, 789 (39%) and 642 (32%) were on peritoneal dialysis and haemodialysis, respectively at the time of transplantation. 5-year renal allograft survival was significantly better in the pre-emptively transplanted group (90.6%) compared to those on peritoneal dialysis and haemodialysis (86.4% and 85.7% respectively; p = 0.02). After accounting for donor type, we found a significantly lower hazard of 5-year renal allograft failure in pre-emptively transplanted children (HR 0.742, p = 0.05). Time spent on dialysis pre-transplant was negatively correlated with renal allograft survival (p = 0.002). There was no significant difference in 5-year renal allograft survival between children who were on dialysis for <6 months and children transplanted pre-emptively (87.5% vs. 90.5%, p = 0.25). Conclusions: Children who are pre-emptively transplanted have improved 5-year renal allograft survival, compared to children on haemodialysis or peritoneal dialysis at the time of transplantation. Although increased time spent on dialysis was correlated with poorer renal allograft survival, we found no evidence that short periods of dialysis (<6 months) pre-transplant affected renal allograft survival in children.